HUBUNGAN PENDAPATAN KELUARGA DENGAN STATUS GIZI BALITA USIA 1-5 TAHUN DI PUSKESMAS KISARAN KOTA TAHUN 2019 - fifi ria (Universitas Prima Indonesia, 2020)
The problem of nutrition because of poverty is the indicator of the family's economic level which is closely related to the purchasing power of the family.This type of research is a descriptive study with a Cross Sectional Survey design. That is a study to challenge the dynamics between risk factors and effects, by utilizing, observing or collecting data at any time (time approach). The population in this study was the family of children under five, taking samples by accidental sampling as many as 50 people. Based on the Chi-Square test results table in the Asyimp.sig column. (2-sided) shows the value (p <0.05), then Ho is rejected and Ha is accepted. It can be concluded that there is a relationship between income and nutritional status of toddlers aged 1-5 years. The conclusion is that there is a relationship between family income and the nutritional status of toddlers aged 1-5 years in Kisaran City Health Center in 2019.